EVALUATION OF "˜DECISION TO DELIVERY INTERVAL' AND CAUSES OF DELAY IN EMERGENCY CAESAREAN SECTIONS IN A TERTIARY CARE HOSPITAL - Fayyaz, Simi; Rafiq, Sonia; Hussain, Shehzadi Saima (Journal of Postgraduate Medical Institute, 2016)
Objective: To evaluate decision to delivery interval in emergency caesarean sections performed in tertiary care hospital and to evaluate the factors caus -ing delay. Methodology: This cross sectional observational study was conducted in De -partment of Obstetrics & Gynaecology, B unit, Lady Reading Hospital from 1 st march 2014 till 31 st august 2014. All emergency caesarean section category A (requiring delivery within 30 min from decision to delivery ) were included and time taken from decision to delivery was noted, in cases where there was delay, the reason was highlighted. Elective caesarean sections and those not requiring urgent caesarean sections were excluded from study. Descriptive statistics were used to analyze the data and results were expressed in per -centages. Results: Total 102 patients were enrolled in this study, in 35.96% (n=41) there was no delay , in 21.05% (n=24) delay was due to non availability of operat-ing table (it was already occupied), delay in arrangement of medicine led to delay in 13.15% (n=15) patients, non-availability of basic investigation (blood group, HBS/HCV) were responsible for delay in 10.52% (n=12) of cases, cross matched blood arrangement was delaying factor in 7% (n=8) of patients, in 1.75% (n=2) of patients delaying in shifting was found .Regarding indications for caesarian section, the commonest indication was fetal distress (n=25, 24.5%) followed by obstructed labour (n=21, 20.5%). Conclusion: caesarean section within 30 minutes is possible, ensuring med-icine availability and increasing the number of operating tables available for surgery will lead to drastic improvement in achieving our goal.